Analysis Of Motivation And Work Discipline On Employee Performance At SMK Negeri 1 Binjai - Alfira Ramadhina; Sri Rahayu; Wilchan Robain (Yayasan Multidimensi Kreatif, 2025)
The research analysis aims to determine the influence of Motivation and Work Discipline on Employee Performance at Smk Negeri 1 Binjai. The data analysis technique used is an associative research method with the help of the SPSS version 25 program. This study uses multiple linear regression analysis. The sample in this study was 72 respondents. Primary data collection uses questionnaires. The results showed that the tcount value was 3.522 > the ttable was 1.99 with a significant value of 0.001 < 0.05, then the H1 hypothesis was accepted and H0 was rejected, meaning that leadership had a positive and partially significant effect on employee performance. The test results for the work motivation variable showed at-calculated value of 5.637 > ttable of 1.99 with a significant value of 0.000 < 0.05, then the H2 hypothesis was accepted and H0 was rejected, meaning that discipline had a positive and partially significant effect on employee performance. The results of the simultaneous test or F test prove that the value of F is calculated as 40.491 which is greater than 3.13 and the significant value of 0.000 is less than 0.05 so that it can be concluded that hypothesis 3 is accepted and hypothesis 0 is rejected so that it can be concluded that work motivation and work discipline have a significant simultaneous effect on employee performance.